The Al-Muhasibi And Al-Ghazali Sufism Concept (Intertextuality Study Of Al-Washaya And Al-Munqidz Min Al-Dhalal) - Ula, Miftahul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to reveal the sufism of al-Muhasibi and al-Ghazali in the autobiography of al-Washaya and al-Munqidz min al-Dhalal book and the autobiography intertextuality of al-Washaya and al- Munqidz min al-Dhalal? The primary source used is the book of al-Washayaby al-Muhasibi and al- Munqidz min al-Dhalal by al-Ghazali. The Sufism science based on al-Muhasibi and al-Ghazali is the scientific culmination of various epistemologies the validity of which can be accounted for. Both of them consider that sufism can satisfy their intellectual and spiritual thirst. The intertextual relationship between those two Sufism books can be seen in those two authors' cultural backgrounds. Their intertextual relations are also found in themes, plots, characterizations, and language styles. This research makes a significant contribution to understanding the integration of Sufism with Shari'a as an intellectual and spiritual solution that remains relevant today.